PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS, PRICE EARNING RATIO DAN ECONOMIC VALUE ADDED TERHADAP RETURN SAHAM PADA PERUSAHAAN SUBSEKTOR PROPERTY DAN REAL ESTATE. - Julyana Widjayanti; Risal Rinofah; Mujino Mujino (Journal Competency of Business, 2018)
This study aims to determinethe effect of Debt to Equity Ratio, Return On Assets, Price Earning Ratio, and Economic Value Added on Stock Returns on Property and Real Estate companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. The sampling technique is purposive sampling. Samples were obtained from 11 Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. Based on the results of data analysis shows that Debt to Equity Ratio and Return On Assets have a positive and significant effect on Stock Return, Price Earning Ratio and Economic Value Added have a negative and no significant effect on Stock Return. Together Debt to Equity Ratio, Return On Assets, Price Earning Ratio, and Economic Value Added have a positive and significant effect on Stock Return.